New strategies for inhibition of non‐adrenergic prostate smooth muscle contraction by pharmacologic intervention. Issue 7 (27th February 2019) - Yu, Qingfeng; Gratzke, Christian; Wang, Yiming; Wang, Xiaolong; Li, Bingsheng; Strittmatter, Frank; Herlemann, Annika; Wang, Ruixiao; Tamalunas, Alexander; Waidelich, Raphaela; Stief, Christian G.; Hennenberg, Martin
Abstract : Background: Inhibition of prostate smooth muscle contraction by α1 ‐adrenoceptor antagonists (α1 ‐blockers) is a first‐line medical treatment of lower urinary tract symptoms suggestive of benign prostatic hyperplasia. Increased smooth muscle tone in the hyperplastic prostate may drive urethral obstruction, resulting in bladder outlet obstruction and voiding symptoms. However, efficacy of α1 ‐blockers is limited, as non‐adrenergic mediators including endothelin‐1 and thromboxane A2 (TXA2 ) increase prostate smooth muscle tension in parallel to α1 ‐adrenoceptors. This may maintain urethral obstruction despite therapy with α1 ‐blockers. Consequently, future treatment options with higher efficacy need to target α1 ‐adrenergic and non‐adrenergic contractions simultaneouly. Recently, several compounds were reported to inhibit adrenergic or neurogenic prostate contractions, however, their effects on non‐adrenergic contraction are unknown. Here, we examined effects of inhibitors for Rac‐GTPase, Src family kinases (SFKs), and p21‐activated kinases (PAKs) on non‐adrenergic prostate contractions. Methods: Prostate tissues were obtained from radical prostatectomy. Contractions were studied in an organ bath. Viability of cultured stromal cells was assessed by CCK‐8 assay. Results: Inhibition of α1 ‐adrenergic contractions by Rac inhibitors EHT1864 (100 μM) and NSC23766 (100 μM), and SFK inhibitors AZM475721 (10 μM) and PP2 (10 μM) was confirmed by inhibition of methoxamine‐induced contractions. No effects of the PAK inhibitors FRAX486 (30 μM) and IPA3 (300 μM) on α1 ‐adrenergic contraction were confirmed by absent effects on methoxamine‐inuced contractions. EHT1864 caused inhibition of endothelin‐1‐ and U46619‐induced contractions. EHT1864 reduced the viability of stromal cells concentration‐ and time‐dependently. EHT1864 attenuated KCl‐induced contractions of prostate strips only slightly, so that toxic effects may not account alone for inhibition of agonist‐induced contractions. NSC23766 inhibited U46619‐induced contractions, but not endothelin‐1‐induced contractions. AZM475271 had no effects on endothelin‐1‐ or U46619‐induced contractions, while PP2 inhibited U46619‐ but not endothelin‐1‐induced contractions. FRAX486 caused inhibition of U46619‐induced contractions. IPA3 inhibited U46619‐, but not endothelin‐1‐induced contractions. Conclusions: Of all six inhibitors, EHT1864 seems to be most promising from a translational point of view, as it inhibited TXA2 ‐ and endothelin‐1‐induced besides α1 ‐adrenergic prostate contractions. This reflects divergent pharmacologic profiles of EHT1864 and NSC23766, although both are Rac‐GTPase inhibitors. In vivo, urodynamic effects of EHT1864 and possibly of FRAX486 may exceed those of α1 ‐blockers.